Commercial arbitration and public policy in Spain and in comparative law: special reference to the European Union’s public policy in the judicial review of awards - Agulló Agulló, Diego (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This paper analyses the notion of public policy in the jurisdictional review of commercial arbitral awards in Spain and in comparative law, with particular attention to the public policy of the European Union. This article argues that courts should show deference towards arbitration, interpreting the notion of public policy in a restrictive manner and protecting the autonomy of the arbitration institution, which is so important in international trade. The court should not be able to enter into an assessment of the merits of the award or replace the decision-making work of the arbitral tribunal. This paper supports, among other aspects, a minimalist approach to the jurisdictional review of the award, in accordance with the recent case law of the Spanish Constitutional Court.